zeroes means root of the equations:

**a) ** 4s² - 4s + 1 = 0

(2s)² - 2×2s×1 + (-1)² = 0

compare with a² - 2ab + b² = (a-b)²

(2s-1)² = 0

2s-1 = 0

s = 1/2 both root are equal and 1/2

**b)**

6x² - 3 - 7x =0

6x² - 9x + 2x - 3 = 0

3x(2x - 3) + 1(2x - 3) = 0

(2x - 3)(3x + 1) = 0

2x - 3 = 0

x = 3/2

or

3x + 1 = 0

x = -1/3

**c)**

4u² + 8u = 0

4u(u + 2) = 0

4u = 0

u = 0

or

u + 2 = 0

u = -2

**d)**

t² - 15 = 0

t² - (√15)² = 0

(t-√15)(t+√15) = 0

t-√15 = 0

t = √15

or

t + √15 = 0

t = -√15

**e)**

3x² - x - 4 = 0

3x² - 4x + 3x - 4 = 0

x(3x - 4) + 1(3x - 4) = 0

(3x - 4)(x + 1) = 0

3x - 4 = 0

x = 4/3

or

x + 1 = 0

x = -1